Comparison of Peri-tonsillar Injection of Tramadol with Adrenaline Vs Injection of Normal Saline (Placebo) Before Tonsillectomy in Reducing Per-operative Haemorrhage and Post-operative Pain - Sundas Masood, Aiemen Fatima, Tahira Ikram, Nausheen Qureshi, Rahat Mukhtar, Fatima Shahid (Journal of Rawalpindi Medical College, 2021)
Introduction: Tonsillectomy is one of the most frequent surgical procedures performed in ENT. In the early postoperative period, pain and hemorrhage are considered to be the major cause of morbidity. Different methods of minimizing postoperative pain have been proposed including the use of oral analgesics, infiltration of local anesthetics, and analgesics like levobupivacaine, ketamine, and tramadol. To secure hemostasis during a tonsillectomy, several techniques including ligation, diathermy, and cauterization are used. To minimize these complications, preoperative preparation of the patient is mandatory. This study aimed to find out the efficacy of adrenaline and tramadol in controlling perioperative hemorrhage and postoperative pain respectively. Materials and Methods: A randomized controlled trial was conducted in the ENT department of Benazir Bhutto Hospital Rawalpindi for 6 months (21-11-2016 to 21-5-2017). The data was collected by operating surgeons. A total of 60 patients were included in the study with 1:1 randomization. Simple random sampling was used for the Selection of patients. Patients were divided into two groups. Group A was provided with the peri-tonsillar injection of tramadol with adrenaline while Group B was provided with normal saline injection (Placebo). Both groups were followed for 6 hours to measure mean pain scores and mean hemostasis time. After approval from the ethical review board, consent forms were distributed to patients. An Independent t-test was applied for the comparison of different variables. Results: Among all patients 60(100%), 25 (41%) males, and 35(59%) females. The mean age of patients was 12.2 years ± 4.49 SD. The mean time required for hemostasis was 4.9 minutes ± 1.92 SD. The mean pain scores were 1.3 (mild pain) ±1.12 SD. A statistically significant difference was found with time (p=0.01), mean pain (p=0.00), weight (p=0.00) and age (p=0.00) while insignificant with gender (p=0.06). Conclusion: Peri-tonsillar injection of tramadol with adrenaline during tonsillectomy leads to a significant reduction in per-operative hemorrhage and post-operative pain as compared to injection of normal saline.